Physical properties and band structure of crystals (3HgTe)1–x(Al2Te3)x, doped with manganese - Maryanchuk, P. D.; Dymko, L. N.; Romanishyn, T. R.; Kovalyuk, T. T.; Brus, V. V.; Solovan, M. N.; Mostovoy, A. I. (Technology and design in electronic equipment, 2014)
This paper presents the results of the analysis of magnetic, optical, kinetic properties and band parameters of (3HgTe)1–x(Al2Te3)x crystals doped by manganese. The behaviour of the magnetic susceptibility of the (3HgTe)1–x(Al2Te3)x: crystals can be explained by the presence of Mn–Тe–Mn–Тe clusters or, more precisely, by their transition from a magnetically ordered to a paramagnetic state at Curie temperature Tc. The temperature dependences of electrical conductivity are typical for semiconductor materials. This is due to the increase in carrier concentration with the increase of temperature. The temperature dependence of the Hall coefficient indicates that electrons and holes participate in the transport phenomena in the studied samples (the conductivity is mixed). In (3HgTe)1–x(Al2Te3)x: crystals, the electron mobility decreases with increasing temperature, indicating the predominance of the scattering of the charge carriers on thermal vibrations of the crystal lattice. Thermoelectric power for the samples under investigation possesses negative values and increases in absolute value with the rise of temperature. The optical band gap of the samples was defined from the optical studies. We have measured current-voltage characteristics of n-TiO2/(3HgTe)1–x(Al2Te3)x: and n-TiN/(3HgTe)1–x(Al2Te3)x: heterojunctions at room temperature. The band gap, the matrix element of the interband interaction and the electron effective mass at the bottom of the conduction band were determined from the concentration dependence of the electrons effective mass at the Fermi level.